Investigation on Phytochemical Constituents and Antimicrobial Properties of Crude Flower Extract of Tecoma stans (L.) Juss. ex Kunth - Pulipati, Sowjanya; Babu, P. Srinivasa (Current Aspects in Pharmaceutical Research and Development Vol. 2, 2021)
Since plants are used as therapeutic agents, the present study is designed to evaluate the phytochemical profile and antimicrobial activities of flower of Tecoma stans (L.) ethanolic extract (TSEE) against selective Gram-positive, Gram-negative bacteria in-vitro. Tecoma stans is a flowering perennial shrub belongs to the family Bignoniaceae. The entire plant possesses medicinal value and used for the treatment of various ailments. The dried flowers were extracted by cold maceration process using ethanol. Presence of phytoconstituents such as alkaloids, glycosides, saponins, carbohydrates, tannins, phenolics compounds, steroids and flavonoids were observed. The antimicrobial activity was carried against bacteria like Staphylococcus aureus, Enterococcus faecalis, Bacillus subtilis, Bacillus megaterium, Streptococcus mutans, Escherichia coli, Klebsiella pneumoniae, Pseudomonas aeruginosa and Proteus vulgaris by means of agar well diffusion method. The TSEE extract exhibited moderate to high level of broad-spectrum antimicrobial activities against these microorganisms. The diameters of zone of inhibition range from 20.33±0.57 to 09.33±1.52 mm; the activity was compared with standard tetracycline. MIC was performed by two-fold broth dilution method and the inhibition range was found to be 31.2 mg/ml to 125 mg/ml. The MBC values lies between 62.5 to 150 mg/ml. The results reported in the present work shows evidence that Tecoma stans flowers possess phytochemicals that exhibit broad spectrum antimicrobial activity against tested pathogenic bacteria.